AXONOMIC STUDIES ON PREDATORY COCCINELLID BEETLES AND THEIR SPECIES COMPOSITION IN RICE ECOSYSTEM OF INDOBANGLADESH BORDER - SAMIK CHOWDHURY; PRITIN P. SONTAKKE; T. BOOPATHI; JAYASHREE BHATTACHARJEE; DEBASHRE BHATTACHARJEE; MALSAWMZUALI (The Bioscan, 2015)
Ten genera under four tribes of the family Coccinellidae were collected and identified from Indo Bangladesh border in 2009-2010. They are Brumoides suturalis (Fabricius), Chilocorus nigritus (Fabricius), Coccinella septempunctata Linnaeus, Coccinella transversalis Fabricius, Harmonia octomaculata (Fabricius), Illeis cincta (Fabricius), Micraspis crocea (Fabricius), Propylea sp. nr. japonica (Thunberg), Cryptolaemus montrouzieri Mulsant and Scymnus (Scymnus) nubilus Mulsant. Result also revealed that out of ten coccinellid Harmonia octomaculata (Fabricius) (22.9%), Micraspis crocea (Fabricius) (18.5%), Brumoides suturalis (Fabricius) (12.36%) and Chilocorus nigritus (Fabricius) (9.06%) were major predatory coccinellids beetles in rice ecosystems of Indo- Bangladesh border.